Criticizing the Others or Ourselves? The MacIntyre-Winch Debate and the Idea of Social Criticism - Lotar Rasiński (University of Lower Silesia, 2017)
MacIntyre states in his criticism of Winch's Idea of Social Science... that it is impossible to criticize the practices of societies with different forms of rationality in terms of their own forms of rationality;  these practices must be intelligible within our own rationality. In this way he assumes that the only possible way to criticize other cultures is a "view from outside." Responding  MacIntyre, Winch states that every criticism of other cultures requires "extending of our own ability of understanding." This seems to suggest that the only possible criticism is the "critique of ourselves." This paper attempts to support Winch's position with political argumentation. It refers to the Walzer-Said debate to demonstrate that the logic of social criticism requires reference to the political dimension of domination and the associated concept of emancipation.